Mantle flow and deep electrical anisotropy in a main gateway: MT study in Tierra del Fuego - González Castillo, Lourdes; Bohoyo, Fernando; Junge, Andreas; Galindo-Zaldívar, Jesús; Cembrowski, Marcel; Torres Carbonell, Pablo Juan; Ruiz-Constán, Ana; Pedrera, Antonio; Ibarra, Pedro; Maestro, Adolfo; Ruano, Patricia (Scientific Reports)
Asthenospheric mantle flow drives lithospheric plate motion and constitutes a relevant feature of Earth gateways. It most likely influences the spatial pattern of seismic velocity and deep electrical anisotropies. The Drake Passage is a main gateway in the global pattern of mantle flow. The separation of the South American and Antarctic plates since the Oligocene produced this oceanic and mantle gateway connecting the Pacific and Atlantic oceans. Here we analyze the deep crustal and upper mantle electrical anisotropy of its northern margin using long period magnetotelluric data from Tierra del Fuego (Argentina). The influence of the surrounding oceans was taken into account to constrain the mantle electrical conductivity features. 3D electrical models were calculated to fit 18 sites responses in this area. The phase tensor pattern for the longest periods reveals the existence of a well-defined NW-SE electrical conductivity anisotropy in the upper mantle. This anisotropy would result from the mantle flow related to the 30 to 6 Ma West Scotia spreading, constricted by the subducted slab orientation of the Pacific plate, rather than the later eastward mantle flow across the Drake Passage. Deep electrical anisotropy proves to be a key tool for a better understanding of mantle flow. Fil: González Castillo, Lourdes. Universidad de Granada; España Fil: Bohoyo, Fernando. Instituto Geológico y Minero de España; España Fil: Junge, Andreas. Goethe Universitat Frankfurt; Alemania Fil: Galindo-Zaldívar, Jesús. Universidad de Granada; España Fil: Cembrowski, Marcel. Goethe Universitat Frankfurt; Alemania Fil: Torres Carbonell, Pablo Juan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Ruiz-Constán, Ana. Instituto Geológico y Minero de España; España Fil: Pedrera, Antonio. Instituto Geológico y Minero de España; España Fil: Ibarra, Pedro. Instituto Geológico y Minero de España; España Fil: Maestro, Adolfo. Instituto Geológico y ...